Correlation between pH and surface structural changes on human enamel submitted to different tooth whitening agents - Elossais, André Afif; Bigarella, Gabriela David; Pereira, Nara Rejane Santos; Bigarella, Cesar Antonio; Fernandes, Sonia Maria Batista; Volpato, Luiz Evaristo Ricci; Porto, Thiago Soares; Andrade, Marcelo Ferrarezi de [UNESP]; Segalla, José Claudio Martins [UNESP]; Silva, Pedro Gregol da (Incessant Nature Science Publishers, 2014)
The intense valuation of an esthetic pleasant smile guided the dentistry to bleached tooth due the popularity of whitening treatments. The consequence of it is an increasing interest in searching the effect of peroxides in hard dental tissues. The aim of this work was to analyze qualitatively in vitro the human enamel after three different bleaching treatments: Opalescence PF 10%, White Class 7.5% and Opalescence Xtra Boost 38%, correlating the structural changes in the surface of the enamel with its respective pH. A total of 40 sound human pre-molars were randomly divided into four groups of 10 elements, which had been immersed in artificial saliva during all the experiment. Bleaching protocols followed the recommendations of the respective manufacturers. Each bleached sample and control group were submitted to a scanning electronic microscopy analysis and compared with one another. Bleaching agents used in this experiment had modified the morphologic aspect of the surface of the dental enamel; however, it did not have correlation between the degrees of severity of the alterations and pH. There is a correlation between hydrogen peroxide concentration and changes in the enamel, where G4 showed more severe alterations, followed for G3 and G2.